The high temperature stress responses in the hepatopancreas of Litopenaeus vannamei: from immune dysfunction to metabolic remodeling cascade - Duan, Yafei; Xiao, Meng; Wang, Yun; Huang, Jianhua; Yang, Yukai; Li, Hua (Frontiers in Immunology, 2025)
Sudden fluctuations in environmental temperatures are primarily caused by climate change. Aquatic organisms such as shrimp are poikilothermic animals, making them highly vulnerable to rising water temperatures, which can trigger stress responses and reduce aquaculture productivity. Hepatopancreas is of vital importance to the immunity, metabolism and detoxification of shrimp. In this study, the shrimp Litopenaeus vannamei were continuously exposed to high temperature (HT) stress at 33 °C for 7 days, and the hepatopancreatic histopathology, immune-related indexes, and metabolite patterns were explored. The results showed that HT stress caused abnormal morphological changes in the hepatopancreas of the shrimp, with the hepatic tubules becoming twisted, atrophied, and even ruptured and autolyzed. At the molecular level, stress-related indexes, such as Nrf2, GPx, and HSP70 genes expression were increased, while SOD and HSP90 genes were decreased; immune-related indexes, such as ALF, Crus, and proPO genes expression were increased, whereas Pen3 gene was decreased; inflammation-related genes (JNK and TNFα) and apoptosis-related genes (Casp9 and Casp3) expression were increased; autophagy-related indexes, such as Atg3, Atg16, and Beclin1 genes expression were increased. Furthermore, HT stress caused the alterations in the metabolic patterns of the hepatopancreas, such as amino acid biosynthesis and metabolism, pentose and glucuronate interconversions, pantothenate and CoA biosynthesis, pyrimidine metabolism, and glycerophospholipid metabolism. Functional metabolites, such as tryptophan, arachidonic acid, cinnamic acid derivatives, vitamins, etc., were identified as biomarker candidates. The results revealed that HT stress induced comprehensive histomorphological and functional impairments in the hepatopancreas of L. vannamei through a cascade of oxidative damage, immune dysregulation, and metabolic disturbance.